Effect of Demography Factor and Employee Engagement to Organizational Commitment - Nida Hasanati (Analitika: Jurnal Magister Psikologi UMA, 2018)
Organizational Commitment is important topic  of organizational behavior, as it can affect job satisfaction, organizational citizenship,  turn over, and job performance  . The purpose of this study is to examine the effect of demographic factors (gender,years of experience ) and employee engagement  to organizational commitment . This study used  bank employees as many as 200 people, research instrumentuse Organizational Commitment Questionnaire (OCQ) and Utrecht Work Engagement Scale (UWES-17). Analytical technique is use multiple regression and T- test. The result of analysis shows that demography factor and employee engagement simultaneously effect organizational commitment, besides it found that  between male and female organizational commitment employees is not different.